Implementing a Critical Care Outreach Team : what difference has it made for nurses? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Nursing at Massey University, Albany, New Zealand - Davies, Kathryn Erin (Massey University, 2011)
The aim of this study is to describe the implementation of Critical Care Outreach (CCO) and to understand what difference implementing a Critical Care Outreach Team (CCOT) has made to ward nurses in a secondary level general hospital in New Zealand. A CCOT was established at the study hospital in 2006. The aim was to implement an early warning score, to provide education and to share appropriate intensive care skills from CCOT nurses on the wards. Additionally, patients discharged from the Intensive Care Unit were to be followed up. The difference this made to ward nurses in this hospital was unclear. International studies had reported suboptimal patient care on acute wards and the emergence of CCOTs. Research was warranted to gain an understanding of the impact of the service on ward nurses. The methodology chosen for the study was case study, and was underpinned by Change Management Theory and elements of whole system reform (Fullan, 2010). Fullan’s (2007) Change Management Theory of a three phased approach to change management, initiation, implementation and institutionalisation was selected for the study. Data was collected from a nursing focus group, three interviews, and District Health Board documents related to the CCOT. Interviews and nursing focus group data were analysed by thematic analysis and documents analysed by subject. Implementing the CCOT facilitated the shift of late recognition/late intervention of patients to early recognition/early intervention. An area of whole hospital reform occurred. The use of an early warning score promoted more timely patient review, communication between nurses and doctors, improved observation frequency and an environment of objectivity developed. Nurses benefited from education, were empowered to escalate patient concerns, improved their assessment and specific clinical skills, and reported that they were supported by the CCOT. The CCOT has had a positive effect on the early recognition and early intervention of the physiologically unstable patient. The challenge to New Zealand nursing now is to continue to build on the evidence from this study that CCOT has a beneficial impact on ward nurses. The challenge to the District Health Board is to preserve CCOT to ensure that nurses are supported and late recognition/late intervention is truly a phenomenon of the past.
Keywords: Intensive care nursing; Nursing; Hospital administration; Hospitals; New Zealand; Critical Care Outreach Team